Socialisation as a Transformation Strategy: »Expropriate Deutsche Wohnen & Co.« in its Discursive and Political Context (PROKLA. Journal of Critical Social Science, 2022)
With having won a referendum in 2021, the initiative Expropriate Deutsche Wohnen & Co. (DWE) has made it a realistic option to socialize big real estate corporations in Berlin. Through this, DWE has reactivated the constitutional political tool of socialization. This article analyses DWE’s demands and concepts, situates them in different political discourses, carves out the inherent transformational strategy and illuminates its potentials, but also practical problems and pitfalls in the context of Berlins state politics. It closes by asking how productive the approach is for the left at large.
Keywords: Expopriate Deutsche Wohnen & Co.; Expropriation; Socialization; Transformation; Strategy